Модернізація системи суспільних відносин у трудовій сфері на засадах соціальної відповідальності - Панькова А.Д. (Економіка промисловості, 2015)
Визначено теоретико-методологічні та організаційно-управлінські аспекти розвитку трудової сфери. Обґрунтовано значимість цінності праці та цінності працівника. Розкрито сутність ціннісної раціональності та цілераціональності, а також місце гідної праці в цих процесах. Обґрунтовано пріоритетні напрями модернізації державного управління у трудовій сфері. Определены теоретико-методологические и организационно-управленческие аспекты развития трудовой сферы. Обоснована значимость ценности труда и ценности работника. Раскрыта сущность ценностной рациональности и целерациональности, а также место достойного труда в этих процессах. Обоснованы приоритетные направления модернизации государственного управления в трудовой сфере. The article defines theoretical, methodological, organizational, and managerial aspects of labour sphere. The importance of the value of labour and employee at the modernization of public relations and the essence of value rationality and goal rationality, and the place of decent work in these processes are substantiated. Decent work is the basis of goal rationality, and not the value of rationality. Goal rationality action arises when target, means and results are calculated and weighed rationally. It is substantiated that decent work is the means to create work as a value and enhance the value of labour rights. The advantages of the system of social relations in implementing values of rationality at work are systematized. The priorities for the modernization of public administration at work are substantiated.